Treatment of ischemic heart disease in end-stage kidney disease patients on renal replacement therapy - Yu. V. Semenova; B. L. Mironkov; Ya. L. Poz (Вестник трансплантологии и искусственных органов)
This review paper aims to analyze the problem of diagnosis and treatment of coronary heart disease (CHD), also called ischemic heart disease (IHD), in patients with end-stage renal disease (ESRD). The analysis is based on current literature data. The issues of CHD risk stratification before patient listing for kidney transplantation (KT) and possible difficulties of diagnosing CHD using non-invasive examination methods in ESRD patients are considered. The effectiveness of myocardial revascularization and drug therapy, endovascular and surgical myocardial revascularization, is compared. The paper also discusses the peculiarities of drug therapy, particularly antiplatelet and antihyperlipidemic therapy in the treatment of CHD in dialysis-dependent patients and kidney recipients.